PENERAPAN SUMBER IDE IKAN BROWN GHOST DALAM PEMBUATAN BUSANA COCKTAIL MUSLIMAH MENGGUNAKAN BAHAN BATIK GRINGSING DAN CERUTY BABY DOLL - Maulinah Fauziah; Titin Prihatini (Jurnal Socia Akademika, 2020)
ABSTRACT This study aims to: 1) create a cocktail dress using batik gringsing and ceruty babydoll, 2) make a cocktail dress by applying ornaments patchwork application, 3) know the results of the application of patchwork application on the manufacture of batik gringsing and ceruty babydoll. This research is a type of research development or Research and Development (R&D) and includes qualitative research with objects focused on the process of making Cocktail Clothing with Brown Ghost Fish Idea Source Applying using Batik Gringsing and Ceruty Babydoll with Patchwork Application Decoration reviewed in terms of models. The study was conducted by sampling study because the author only took part of the population, namely matching clothing from batik motifs gringsing and ceruty babydoll. Data collection techniques in this study are: 1) experimental methods are used to see the results of the experiment. 2) Sensory test method is done by level to match and conformity testing. 3) the documentation method in the form of photos of research results. Data analysis techniques are presented and described according to the data obtained by the sensor test results. The stages are carried out as a prayer in conducting the results of research. The results of research on cocktail clothing from batik motif gringsing and ceruty babydoll with ornament application of patchwork at the beginning of preparing cocktail fashion design packages, preparing sizes and patterns, preparing materials, preparing ornaments or ornaments, and preparing tools - experimental tools. Sensory test data aims to determine the panellist's reaction to the model, the suitability of patchwork application decoration and the total look of the experiment. Based on sensory test results, cocktail fashion in terms of decoration fit model and total look is preferred